Software Development for Education Infrastructure Management: Extreme Programming-Based Approach - Denny Jean Cross Sihombing (Kesatria : Jurnal Penerapan Sistem Informasi (Komputer dan Manajemen), 2024)
Education infrastructure in Indonesia faces significant challenges and inequity between urban and rural areas. Differences in education facilities, teacher qualifications, and access to technology are key issues in improving the quality of education across the country. In this context, an efficient education infrastructure system and the software applications that support it are crucial to achieving educational equity. This study adopted the Extreme Programming (XP) software development method to develop an education infrastructure application focusing on school data management. The results of this study show that the education infrastructure application based on the XP method successfully identified the initial requirements strongly and focused on the most essential features. User Acceptance Testing (UAT) provided valuable feedback, highlighting the strengths and weaknesses of the application; the user satisfaction rate was 82%. It was found that the app has the potential to fulfil user needs, although some improvements are needed, especially in certain features such as the Inventory module. Future research could focus on the continued development of the education infrastructure app, taking into account user suggestions and feedback. Further research involves more stakeholders, including parents and students, in testing and improving the app. This research highlights the importance of developing software applications that support equitable and efficient education infrastructure in Indonesia.